Active energy losses research in an asynchronous electric motor in operating terms - Овчаров, Сергей; Стребков, Александр Андреевич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents the results of an analytical active power losses research in an asynchronous electric motor with a squirrelcage rotor in a function of operating parameters. The studies were conducted due to the fact that the electric motor operating modes at other deviations from the nominal operating mode: overvoltage, undervoltage, open-phase operating conditions, deterioration of cooling conditions, ambient temperature increase remain unexplored. An improved equivalent circuit of the asynchronous electric motor with the squirrel-cage rotor taking into account active losses of power for eddy electric currents and hysteresis in the magnetic core was proposed. An expression of active power losses in the electric motor coils taking into account the coil heating and the ambient temperature was derived. The concept of the factor of active power losses in the electric motor as the ratio of active power losses in the electric motor to the active power on its shaft was introduced. The dependence of the factor of active power losses in a function of power on its shaft, allowing to optimize the electric motor operating mode was investigated. A pie chart of power losses in the asynchronous electric motor in a function of its slip was proposed. The obtained research results allow to take into account the active energy losses in the asynchronous electric motor at all operationg deviations from the nominal operating mode.